Does a physical activity program in the nursing home impact on depressive symptoms?: a generalized linear mixed-model approach - Diegelmann, Mona; Jansen, Carl-Philipp; Wahl, Hans-Werner; Schilling, Oliver; Hauer, Klaus (Aging & mental health, 2018)
Objectives: Physical activity (PA) may counteract depressive symptoms in nursing home (NH) residents considering biological, psychological, and person-environment transactional pathways. Empirical results, however, have remained inconsistent. Addressing potential shortcomings of previous research, we examined the effect of a whole-ecology PA intervention program on NH residents’ depressive symptoms using generalized linear mixed-models (GLMMs). Method: We used longitudinal data from residents of two German NHs who were included without any pre-selection regarding physical and mental functioning (n = 163, Mage = 83.1, 53-100 years; 72% female) and assessed on four occasions each three months apart. Residents willing to participate received a 12-week PA training program. Afterwards, the training was implemented in weekly activity schedules by NH staff. We ran GLMMs to account for the highly skewed depressive symptoms outcome measure (12-item Geriatric Depression Scale-Residential) by using gamma distribution.Results: Exercising (n = 78) and non-exercising residents (n = 85) showed a comparable level of depressive symptoms at pretest. For exercising residents, depressive symptoms stabilized between pre-, posttest, and at follow-up, whereas an increase was observed for non-exercising residents. The intervention group's stabilization in depressive symptoms was maintained at follow-up, but increased further for non-exercising residents.Conclusion: Implementing an innovative PA intervention appears to be a promising approach to prevent the increase of NH residents’ depressive symptoms. At the data-analytical level, GLMMs seem to be a promising tool for intervention research at large, because all longitudinally available data points and non-normality of outcome data can be considered.